SUBMICROSCOPIC ORGANIZATION OF STRUCTURAL COMPONENTS OF INTACT WHEAT RATS’ TESTICLES - Volkov, K.S.; Mukha, S.U. (World of Medicine and Biology, 2018)
The morphofunctional state studies of the testes’ (testicles’) structural components under normal conditions of the human male and intact animals’ male body are topical until now [1, 2]. Peculiarities of the spermatogenic epithelium ultrastructural organization at different phases of spermatogenesis have not been completely studied. The present study was aimed to establish the peculiarities of the structural components’ electron microscopic organization in testicles of the intact white laboratory animals. Experiments were carried out on 8 sexually mature white male rats. The material for electron microscopic study was processed in accordance with the generally accepted procedure. Prepared small pieces of testes were fixed in 2.5% glutaraldehyde solution, postfixation was carried out with 1% solution of osmium tetroxide, dehydrated in propylene oxide and poured into a mixture of epoxy resins with araldite. Ultra-thin sections were contrasted with a 1% aqueous solution of uranyl acetate and lead citrate by the Reynolds method and studied with PEM-125K electron microscope. The performed electron microscopic examination of the intact animals’ testes showed that in the loose connective tissue of the organ’s stromas, vessels of the microcirculatory bed were located. Blood capillaries have moderate lumens, in which formed blood elements are observed. The inner part of the hemocapillary wall forms oblong shaped endothelial cells that have thickened nucleated areas and thin cytoplasmic areas. The former include the ellipsoid nucleus and the cytoplasm, which contains most organelles of the endothelial cells. In the cytoplasmic area, mainly pinocyte bubbles, caveoli, and rare organelles are localized. The basement membrane, on which the endothelial cells are located, separates them from the perivascular areas of the loose connective tissue. Quite large Leydig cells - testicular endocrinocytes - contact with the blood capillaries. They have a large area of the cytoplasm and, mostly, nuclei of the round form. Their characteristic feature is the presence of lipid inclusions and small electron-dense hormonal granules in the cytoplasm. Three layers are characteristic of ultrastructural organization of the convoluted tubule’s wall: basal, myoid and fibrous. The basis of the internal basal layer is the net of collagen fibers, and on its basement membrane spermatogenic epithelium is located. Myoid cells of the middle layer are similar to myocytes of the smooth muscle tissue. In their cytoplasm there are many myofilaments and caveoli. Such a structure of this layer provides contraction of the tubule’s wall, which helps the sperm release. The inner contents of the tubules are the sustentocytes - supporting cells and spermatogenous cells (spermatogonia, spermatocytes of the first and second order, spermatids and spermatozoa) that are located at different successive phases of spermatogenesis. Electron microscopically supporting cells have a large cone-shaped body with sprouts, which are anastomosed with each other and form micro-environment to cells of the spermatogenic epithelium. Spermatogenic cells are in close contact with plasmallemma of the sustenocytes. Reproduction (mitotic division) of spermatogonia provides spermatocytogenesis which is the first stage of spermatogenesis. In the growth phase, primary spermatocytes have a significant cytoplasmic area, which is electron-light, includes many free ribosomes and small, unevenly located mitochondria. The cells have meiotic figures. In the ripening phase, secondary spermatocytes are formed of the primary spermatocyte, which are smaller in size, include round euchromatic nuclei, a small cytoplasm area and are localized closer to the lumen of the convoluted tubule. Plasmalemmas of spermatocytes are closely interconnected with each other and form cytoplasmic bridges, forming a peculiar multicellular structure - syncytium. The second stage of maturation leads to formation of small spermatoid cells. They, depending on the spermiogenesis stage, have a number of ultrastructure transformations in the nucleus and the cytoplasm at the formation phase. The peculiar structure of the spermatosoid head is an acrosome formed of the Golgi complex components. In the process of the Golgi complex transforming into acrosomes a number of ultrastructural transformations takes place. In the process of formation there is a protrusion of the nucleus with an acrosome outside the cytoplasm. Centrioles move to the cytoplasm area, which is located behind the nucleus, the proximal one is placed near it, and the distal one participates in the spermatic filament formation. In the anti-acrosomal area, mitochondria and microtubules are concentrated, which causes prolongation of spermatid and formation of the spermatozoid’s tail. Mitochondria are located spirally around dense fibers of the intermediate tail sector, forming a mitochondrial pelvic. The formation phase ends with the release of sperm from the syncytium, moving them to the lumen of the seminal tubule. Electron- microscopicic studies of intact white rats’ testicles have identified the features of the stroma’s thin structure, Leydig cells, hemocapillaries, walls of the convoluted seminal tubule, supporting and spermatogenous cells associated with the performance of specific functions.